Odpowiedzi

2009-12-01T17:08:44+01:00
3x+y =4
6x- (1-3y)= 7

3x+y=4
6x-1+3y=7

3x+y=4 |* -2
6x+3y=8

-6x-2y=-8
6x+3y=-8
y=0

3x+y=4
3x=4-y
3x=4-0=4
x=4/3

Jedna część zadania ;)






2009-12-01T17:09:12+01:00
3x+y=4
6x-(1-3y)=7

3x+y=4
6x-1+3y=7

3x+y=4
6x+3y=7+1

3x+y=4 /*(-3)
6x+3y=8

-9x-3y=-12
6x+3y=8
------------- dodajemy
-3x=-4 /*(-1)
3x=4
x=4/3
x=1 ⅓

3*1⅓+y=4
4+y=4
y=4-4
y=0

2009-12-01T17:10:38+01:00
3x+y=4
6x-(1-3y)=7

3x+y=4
6x-1+3y=7

3x+y=4 |*(-2)
6x+3y=8

-6x-2y=-8
6x+3y=8

y=0

3x+y=4
3x+0=4

3x=4
x=1 i1/3